A taxonomic review of the genus Dicranorhina Shuckard (Hymenoptera: Crabronidae: Crabroninae) from the Indian subcontinent with the description of three new species from Southern Western Ghats - Mawadda, N.v. Ayisha; Kumar, P. Girish; Sureshan, P.m.; Rajan, Tessy (Zootaxa, 2019)
The genus Dicranorhina Shuckard, 1840, is reviewed from the Indian subcontinent. Three new species namely D. dinesani Mawadda, Girish Kumar & Sureshan sp. nov., D. georgei Mawadda, Girish Kumar & Sureshan sp. nov., and D. sreeramani Mawadda, Girish Kumar & Sureshan sp. nov., are described from the Southern Western Ghats of Kerala. Differences to similar species are given and a revised key to species of the Indo-Australian and Pacific regions is provided.